The sixth station - Stasi, Linda (Forge, 2013)
Some say Demiel ben Yusef is the world's most dangerous terrorist, personally responsible for bombings and riots that have claimed the lives of thousands. Others insist he is a man of peace, a miracle worker...even the Son of God. His United Nations trial in New York City for crimes against humanity attracts mobs of protestors, as well as media from around the world. Feisty reporter Alessandra Russo is covering the tribunal and hoping for a story. But when ben Yusef approaches her in the crowd, he does something so bizarre it stuns the world and hurls Alessandra into a murderous conspiracy of apocalyptic proportions. Running for her life, she must elude assassins, unearth the hidden bond between the shadowy Cathars and the Knights Templar, and uncover a mysterious relic stained with the blood of Christ.